Developing women leaders within organisations: why it makes business sense - Siwadi, Patience (Faculty of Business, University of Botswana, 2016)
In marrying two contemporary issues, leadership and women leaders, it is apparent that women are introducing new leadership styles to organizational settings evident in the way in which organizations have for 20 years or so, sought to encourage men to behave like women. Notions of contemporary leadership, extol the virtues of sensitivity, good communication, emotional management, a sense of community by en large feminine characteristics (Covey, 1992, 1998; Bennis and Nanus, 1997). In other words, male leaders are thought to lack characteristics which would improve their leadership performance. This concept paper argues that by not developing women leaders, organizations are selling themselves short instead of tapping into the feminist attributes that seem more suited to today’s organizations. The paper indicates the qualities of women leaders which are currently forgone the world over, where women leaders are hardly 25% of the working women. The paper utilized desk research as well as personal experiences to develop and augment this argument.